Comparison of two pediatric cases requiring the use of bivalirudin during cardiopulmonary bypass. (October 2018) - Bryant, Molly E.; Regan, William L.; Fynn-Thompson, Francis; Hoganson, David; Nasr, Viviane G.; Zaleski, Katherine; Faella, Katie; Matte, Gregory S.
Introduction: Comparison of two pediatric cases at our institution that utilized bivalirudin for anticoagulation on cardiopulmonary bypass (CPB); a bilateral lung transplant (BLT) and a ventricular assist device (VAD) implantation. Methods: The same bivalirudin protocol was utilized in both cases with an initial bolus of 1 mg/kg administered by the anesthesia team, a 50 mg bolus in the pump prime at the time of the initial patient bolus and an initial infusion rate of 2.5 mg/kg/h, with titration as needed during CPB to maintain kaolin-activated clotting time (K-ACT) values >400 s. Results: The BLT experienced high K-ACT levels (>720 s) for the majority of the case despite decreasing the bivalirudin infusion rate to 0.5 mg/kg/h. The VAD implantation case required the bivalirudin infusion rate to be increased to 5.0 mg/kg/h throughout the case due to low K-ACTs. Conclusion: The literature strongly supports a specific infusion rate 1–7 (2.5 mg/kg/h) for bivalirudin anticoagulation during extracorporeal circulation. Clinicians must consider the loss of clotting factors and the administration of blood products while adjusting the bivalirudin infusion during bypass. We have now elected to maintain an infusion rate of ≥0.5 mg/kg/h for bivalirudin anticoagulation at our center, based on institutional experience, though consideration for a higher infusion rate for an added margin of safety should be considered. It is imperative to have a well-developed protocol for the management of these cardiopulmonary bypass patients and we offer our one-page timeline of events to help guide other pediatric centers looking to use bivalirudin anticoagulation.